Novel differential power processing technique for uneven partial shading mitigation in PV systems - Murkute, Subhash; Kulkarni (Deodhar), Vandana Abhay (Institute of Advanced Engineering and Science, 2024)
Photovoltaic (PV) system output power greatly depends on environmental operating conditions. Partial shaded condition (PSC) operates PV string under mismatch. PV module mismatch has been one of the major causes for reduced amount of output power. Maximizing the amount of energy extraction from PV system under mismatch greatly influenced by conversion efficiency as well as the mismatch mitigation topology used. Differential power processing (DPP) is one of the advanced techniques to deal with mismatch conditions and enhance power output from a PV system. In this paper hybrid modular DPP topology is presented. The proposed technique mitigates the effect of mismatches at submodule and enhance power extraction from PV string. Since in majority shading on a PV module is nonuniform. The conversion efficiency of module level DPP shading mitigation techniques enhanced using submodule level DPP architecture. To demonstrate its applicability simulation study is carried out in MATLAB Simulink and results are compared with traditional bypass method and module level DPP. Simulation results showed the reduction in mismatch loss and improvement in efficiency and power output.